Thrombotic thrombocytopenic purpura misdiagnosed as autoimmune cytopenia: Causes of diagnostic errors and consequence on outcome. Experience of the French thrombotic microangiopathies reference centre. Issue 4 (21st February 2017) - Grall, Maximilien; Azoulay, Elie; Galicier, Lionel; Provôt, François; Wynckel, Alain; Poullin, Pascale; Grange, Steven; Halimi, Jean‐Michel; Lautrette, Alexandre; Delmas, Yahsou; Presne, Claire; Hamidou, Mohamed; et al.
Abstract: Thrombotic thrombocytopenic purpura (TTP) has a devastating prognosis without adapted management. Sources of misdiagnosis need to be identified to avoid delayed treatment. We studied 84 patients with a final diagnosis of severe (<10%) acquired ADAMTS13 deficiency‐associated TTP from our National database that included 423 patients, who had an initial misdiagnosis (20% of all TTP). Main diagnostic errors were attributed to autoimmune thrombocytopenia, associated (51%) or not (37%) with autoimmune hemolytic anemia. At admission, misdiagnosed patients were more frequently females ( P = .034) with a history of autoimmune disorder ( P = .017) and had organ involvement in 67% of cases; they had more frequently antinuclear antibodies ( P = .035), a low/undetectable schistocyte count ( P = .001), a less profound anemia ( P = .008), and a positive direct antiglobulin test (DAT) ( P = .008). In multivariate analysis, female gender ( P = .022), hemoglobin level ( P = .028), a positive DAT ( P = .004), and a low schistocytes count on diagnosis ( P < .001) were retained as risk factors of misdiagnosis. Platelet count recovery was significantly longer in the misdiagnosed group ( P = .041) without consequence on mortality, exacerbation and relapse. However, patients in the misdiagnosed group had a less severe disease than those in the accurately diagnosed group, as evidenced by less organ involvement at TTP diagnosis ( P = .006). TTP is frequently misdiagnosed with autoimmune cytopenias. A low schistocyte count and a positive DAT should not systematically rule out TTP, especially when associated with organ failure.